The Pritzker Architecture Prize and its potential for developing library tourism - Hristov, Radoslav (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
Star architecture is becoming a popular strategy for urban solutions, and exclusive projects are being constructed to create an image and increase media attention. The term describes buildings designed by famous architects who often capitalize on their popularity for marketing purposes in tourist destinations. The visibility of these sites effectively attracts tourists and capital to specific places. It is common for landmark buildings and their leading architects to be paired with the Pritzker Architecture Prize. This paper reviews all 72 libraries designed by prize winners from the first edition in 1979 to 2023, analyzing their potential for library tourism. The research methodology includes a documentary and content analysis (internal and online desk research) of websites, newsletters, and publications. It can be concluded that these libraries have a vast collection of resources that can entice tourists, and now they are destinations for millions of visitors. On the other hand, the authority of these architects guarantees the more significant popularity of libraries as tourist destinations. However, given the financial resources needed to implement these projects, their tourism potential can mainly benefit large cities in developed countries or traditional academic centers.